2017
DOI: 10.1097/aci.0000000000000338
|View full text |Cite
|
Sign up to set email alerts
|

Microbes, allergic sensitization, and the natural history of asthma

Abstract: Purpose of review Understanding factors that lead to asthma development in early life is essential to developing strategies aimed at primary or secondary prevention. Recent findings This article will review current evidence addressing the development of early life allergic sensitization in relation to microbes and the gut and airway microbiome. Wheezing illnesses, particularly viral, remain a significant risk factor for asthma inception; however, bacterial pathogens have recently emerged as an additional imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 53 publications
1
13
0
1
Order By: Relevance
“…In a US general adult population sample (≥65 years) with active asthma, patients with COPD had a four-fold higher risk of having asthma-related hospitalizations in the last 12 months [ 26 ]. A similar result was found in a Canadian study, using health administrative databases: higher rates of asthma claims were found in patients with than in those without COPD [ 27 ]. Moreover, active asthma was significantly associated with an increased risk for chronic bronchitis, emphysema, and COPD over a 20-year follow-up [ 28 ].…”
Section: Discussionsupporting
confidence: 87%
“…In a US general adult population sample (≥65 years) with active asthma, patients with COPD had a four-fold higher risk of having asthma-related hospitalizations in the last 12 months [ 26 ]. A similar result was found in a Canadian study, using health administrative databases: higher rates of asthma claims were found in patients with than in those without COPD [ 27 ]. Moreover, active asthma was significantly associated with an increased risk for chronic bronchitis, emphysema, and COPD over a 20-year follow-up [ 28 ].…”
Section: Discussionsupporting
confidence: 87%
“…Feng et al (2016) reported that parental allergic diseases, atopy, diet and early life exposures might explain the higher prevalence of asthma in the urban environment. Also, there is a complex interplay between genetic predisposition and environmental exposures, including microbes and allergens (Anderson and Jackson, 2017). Regarding exposure to molds, it is estimated that in France about 125,000 individuals suffer from severe asthma with fungal sensitization (SAFS) episodes (189 cases/100,000 adults per year) (Gangneux et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Wheezing illnesses in the preschool age population are common and associated with significant morbidity and cost. 1,2 Risk of asthma and wheeze in this age group is multifactorial with genetic and environmental contributions, 3,4 and the presence of allergic sensitization has been linked to asthma that persists later in life. 5 Environmental and behavioral changes, including dietary factors, may be major contributors to childhood asthma risk.…”
mentioning
confidence: 99%